2000
DOI: 10.1007/s101520050030
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase activity and biomineralization process in embryos, larvae and adult blue mussels Mytilus edulis L.

Abstract: To decide whether a physiological role can be attributed to enzymatic activity with respect to crystal formation and biomineralization of the first larval shell, carbonic anhydrase (CA) activity was measured in embryos and larvae of the blue mussels Mytilus edulis L. Also, CA activity was determined in the mantle edge and gonads of adult mussels with different shell length and condition index. The intention was to find a possible correlation between CA activity and adult shell calcification, i.e. gonadal matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…Cruise Sal TA (μmol kg −1 ) DIC (μmol kg −1 ) TOxN (μmol l −1 ) Si (μmol l −1 ) PO 4 (μmol l −1 ) pH pCO 2 (μatm) (Medaković 2000). Since aragonite is 50 % more soluble than calcite, these aragonitic larval stages of molluscs are expected to be more sensitive to ocean acidification than calcitic organisms.…”
Section: Estuarymentioning
confidence: 99%
“…Cruise Sal TA (μmol kg −1 ) DIC (μmol kg −1 ) TOxN (μmol l −1 ) Si (μmol l −1 ) PO 4 (μmol l −1 ) pH pCO 2 (μatm) (Medaković 2000). Since aragonite is 50 % more soluble than calcite, these aragonitic larval stages of molluscs are expected to be more sensitive to ocean acidification than calcitic organisms.…”
Section: Estuarymentioning
confidence: 99%
“…In Mytilus larvae, high expression of carbonic anhydrase was found to precede formation of the shell field in the gastrula stage, formation of the shell gland and periostracum in the trochophore stage, and mineral deposition in the prodissoconch-I and prodissoconch-II stages (Medakovic, 2000). Although the carbonic anhydrase II used in this study was not extracted from C. gigas or bivalves, this enzyme catalyzes carbonic dehydrogenation in all species, and was judged to be appropriate in this study.…”
Section: Discussionmentioning
confidence: 97%
“…2). Moreover, many of researchers reported that the organic matrices determine the metamorphosis of bivalve shell from embryo to juvenile stage (Medakovic, 2000;Weiss et al, 2002;Lee et al, 2006a) (Fig. 3).…”
Section: The Definition Of ''Biocatalyst''mentioning
confidence: 94%
“…5). The activity of carbonic anhydrase and its influence on physiological function in mollusks have been extensively investigated (Wilbur and Anderson, 1950;Nielsen and Frieden, 1972;Arnold and Holland, 1976;Wilbur and Saleuddin, 1983;Miyamoto et al, 1996;Duvail et al, 1998;Medakovic, 2000;Henry et al, 2003;Yu et al, 2006). The role of carbonic anhydrase on shell formation through the conversion of CO 2 to HCO 3 À and CO 3 2À may be divided into four steps ( Fig.…”
Section: Background To Co 2 Storage Using Biocatalystsmentioning
confidence: 99%
See 1 more Smart Citation